Genomic Analysis of Fungal Species Causing Ascochyta Blight in Field Pea - Turo, Chala Jefuka (Curtin University, 2016)
Peyronellaea pinodes, Peyronellaea pinodella, Ascochyta pisi and Phoma koolunga are the most destructive fungal pathogens of Pisum sativum. Genomic and transcriptomic analysis indicated that these pathogens evolved plant cell wall de-polymerization arsenals as host adaptation. Two necrosis-inducing proteins from P. pinodes were functionally characterized. About 123 – 226 putative effector proteins were predicted. Availability of these data will provide a genome genomebased platform allowing opportunities for further advancements in pea disease management and development of novel effector based breeding techniques.